INHIBITORY ACTIVITY OF LUPEOL FROM Cryptolepis oblongifolia (MEINS) SCHLTR ON PARTIALLY PURIFIED PHOSPHOLIAPASE A2 VENOM OF Naja nigricollis (ELAPIDAE) - Umar, Saifullahi; Ibrahim, S. I.; Namadina, M. M.; Ahmed, A.; Abdullahi, B. S. (FUDMA JOURNAL OF SCIENCES, 2023)
The research is design to provide scientific evidence for the use of Cryptolepis oblongifolia in traditional treatment of inflammation and also to examine whether it have some snake venom phospholipase A2 inhibition potential. A triterpene was isolated from C. oblongifolia using column chromatography and identified via spectroscopic means. The inhibitory activity of the isolate on phospholipase A2 (PLA2) of Naja nigricollis venom was evaluated. The proton nuclear magnetic resonance (1H NMR) of the isolated compound showed the presence of olefinic protons while the carbon nuclear magnetic resonance (13C NMR) showed the presence of exomethylene carbon atoms. By comparison with the reported literature the compound was found to be lupeol, the inhibitory activity of the isolate on PLA2 of Naja nigricollis venom showed that, the isolate inhibits the PLA2 at dose dependent manner with inhibition binding constant (ki) of 0.015 mg/ml. The activity of the compound isolated supports the local usage of C. oblongifolia in traditional treatment of inflammation.
Keywords: Inhibition; Lupeol; Naja nigricollis; Phospholipase A2